Análise comparativa entre técnicas de otimização de eficiência para acionamento e controle de velocidade de motores de indução trifásicos - Zottis, Rafael (2014)
This monograph presents comparative study of techniques to minimize losses to the speed control of induction motors. Induction motors have been widely used in industry because of the low cost and reliability, resulting in a significant portion of electricity consumption. In this sense, the drive of induction motors efficiently for a wide operating range of torque and speed is of invaluable importance. For this, it is necessary to use online and offline techniques in order to improve the efficiency of induction motors in order to seek maximum efficiency under different torque and speed. Initially it is a review of three-phase induction motors, which are some characteristics, operation and losses that arise on the engine. During the work is done the modeling engine to the rotor flux reference frame, in which the generic framework of park was used, this way the transfer function of the machine model is presented and then made the design of the controllers to then calculate the gains of the controllers. In order to perform a comparative analysis between the main techniques of online and offline optimization to minimize losses in the drive induction motors, this paper: (i) a literature review is presented, (ii) implementing algorimos in Matlab / Simulink, and finally (iii) comparing and discussion the results obtained.